Hydrodynamical model atmospheres: their impact on stellar spectroscopy and asteroseismology of late-type stars - Ludwig, Hans-Günter; Steffen, Matthias (Arxiv, 2016)
Hydrodynamical, i.e. multi-dimensional and time-dependent, model atmospheres of late-type stars have reached a high level of realism. They are commonly applied in high-fidelity work on stellar abundances but also allow the study of processes that are not modelled in standard, one-dimensional hydrostatic model atmospheres. Here, we discuss two observational aspects that emerge from such processes, the photometric granulation background and the spectroscopic microturbulence. We use CO5BOLD hydrodynamical model atmospheres to characterize the total granular brightness fluctuations and characteristic time scale for FGK stars. Emphasis is put on the diagnostic potential of the granulation background for constraining the fundamental atmospheric parameters. We find a clear metallicity dependence of the granulation background. The comparison between the model predictions and available observational constraints at solar metallicity shows significant differences, that need further clarification. Concerning microturbulence, we report on the derivation of a theoretical calibration based on CO5BOLD models, which shows good correspondence with the measurements for stars in the Hyades. We emphasize the importance of a consistent procedure when determining the microturbulence, and point to limitations of the commonly applied description of microturbulence in hydrostatic model atmospheres.